2007
DOI: 10.1001/jama.298.19.2275
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Related Plasma Hemodilution and PSA Concentration Among Men With Prostate Cancer

Abstract: HE PREVALENCE OF OBESITY IN the United States has dramatically increased in the past decade. 1 Increased body mass index (BMI) has been linked to death from colon, breast, and many other cancers. 2 Although there are biological bases for increased risk of certain cancers in obese persons, 3 delayed diagnosis may provide an explanation for advanced stage of disease and poor outcome. Obesity presents technical problems for cancer detection, since adiposity may hinder physical examination and interfere with imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
306
10
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(351 citation statements)
references
References 35 publications
30
306
10
5
Order By: Relevance
“…However, we have done this earlier in this exact same cohort and noted that obese men are more likely to develop a biochemical recurrence, 10 though longer follow-up with more distal end-points such as metastasis and cancer death are needed. Finally, obese men have lower PSA values than normal weight men, 22 which theoretically could lead to delayed diagnosis. As such, this is a possible explanation for the larger sized tumors at ultimate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have done this earlier in this exact same cohort and noted that obese men are more likely to develop a biochemical recurrence, 10 though longer follow-up with more distal end-points such as metastasis and cancer death are needed. Finally, obese men have lower PSA values than normal weight men, 22 which theoretically could lead to delayed diagnosis. As such, this is a possible explanation for the larger sized tumors at ultimate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…11 This explanation was validated by Branz and co-workers study on prostate cancer patients. [12][13][14] The main aim of this study was to find a useful clinically applied equation based on the already established PSA-BMI correlation, as well as to test our hypothesis based on this equation, we applied this equation in randomly selected previously biopsied cases, comparing our data with Oesterling et al 5 We are not referring to the use of any of TRUS data (that is, volume and density). This is based on two reasons; first is the subjective error that could be countered during measurements; and second is our aim itself, which is supplying an equation before any invasive maneuver (TRUS).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In addition, obesity correlates with a number of clinical variables, including serum PSA level and prostate volume, in patients with prostatic disease. [5][6][7] Several studies from western countries have shown that obesity predisposes to recurrent PCa with more aggressive pathological features and/or higher biochemical recurrence rates after radical prostatectomy (RP). [8][9][10][11][12][13][14] In addition, obese men were reported to be at greater risk of developing higher-grade tumors after surgery in low-risk PCa matched the criteria of active surveillance programs.…”
Section: Introductionmentioning
confidence: 99%